THE VALUE RELEVANCE OF EARNING MEASUREMENT USING OHLSON MODEL: A META-ANALYSIS - Karyadi, Hari; Subroto, Bambang; Rahman, Aulia Fuad; Maski, Ghozali (Accounting Department,, 2018)
The researchers of accounting information value relevance using Ohlson model had operationalized several earnings measurement proxies. The results of the studies indicated that the level of value relevance and significance influence of each proxy varied. This research aimed to combine this diversity and reveal which earnings measurement proxy has significant value relevance. Meta-analysis of 97 published studies using Ohlson model confirmed the significant relationship between earnings and equity market values. This significant relationship was found in the measurement proxy of abnormal earnings, extraordinary earnings before items, earnings per share and net income. Meta-analysis also found that for proxy net income measurement required investigation of moderating variables.